2013
DOI: 10.5482/hamo-13-04-0026
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary thrombotic thrombocytopenic purpura and the hereditary TTP registry

Abstract: SummaryHereditary thrombotic thrombocytopenic purpura (TTP), also known as Upshaw-Schulman syndrome, is a rare recessively inherited disease. Underlying is a severe constitutional deficiency of the von Willebrand factor-cleaving protease, ADAMTS13, due to compound heterozygous or homozygous mutations in the ADAMTS13 gene. The clinical picture is variable and more and more patients with an adult-onset are diagnosed.In the majority of countries the only available treatment is plasma, which when administered regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 46 publications
0
18
0
4
Order By: Relevance
“…From two congenital TTP cohorts, that of the Hemostasis Research Laboratory in Bern, Switzerland [10,11] and the Japanese congenital TTP study [4], confirmed congenital TTP patients were selected based on the following two criteria: a) the patient had not been extensively studied by other groups and b) whole blood for DNA extraction was available. A total of 32 congenital TTP patients (30 from Europe and 2 from Japan) were included in this study, of which thirteen had severe renal insufficiency up to end-stage renal disease ( Table 1).…”
Section: Patientsmentioning
confidence: 99%
“…From two congenital TTP cohorts, that of the Hemostasis Research Laboratory in Bern, Switzerland [10,11] and the Japanese congenital TTP study [4], confirmed congenital TTP patients were selected based on the following two criteria: a) the patient had not been extensively studied by other groups and b) whole blood for DNA extraction was available. A total of 32 congenital TTP patients (30 from Europe and 2 from Japan) were included in this study, of which thirteen had severe renal insufficiency up to end-stage renal disease ( Table 1).…”
Section: Patientsmentioning
confidence: 99%
“…33,34 Analysis of VWF multimers was performed using sodium dodecyl sulfate-agarose gel electrophoresis followed by western blotting and sensitive luminescence detection. 4,35 VWF degradation products generated by ADAMTS-13-mediated cleavage were assessed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis under reducing conditions followed by western blotting and immunostaining with a horseradish peroxidase-labeled polyclonal rabbit antihuman VWF antibody with enhanced chemiluminescence detection. 4,35,36 …”
Section: Adamts-13 and Vwf Assaysmentioning
confidence: 99%
“…3 The congenital form of TTP (cTTP, previously termed hereditary TTP or Upshaw-Schulman syndrome) is an ultrarare, although likely underestimated, condition with a prevalence of approximately 1 case per million. 4,5 It exhibits an autosomal recessive mode of inheritance caused by homozygous or compound heterozygous mutations in both ADAMTS-13 alleles on chromosome 9. 6 The nature of the mutations is diverse and includes single amino acid missense substitution (approximately 60%), as well as nonsense, frame-shift, splice site mutations and deletions and insertions (collectively, approximately 40%).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, regular plasma infusions-of which the number depends on the patient's phenotype-may prevent acute TTP episodes. [11][12][13] Lifelong treatment with plasma, however, is inconvenient, and administration of plasma may result in fluid overload or elicit allergic reactions to plasma proteins. The risk of viral/prion transmission also remains a major concern.…”
mentioning
confidence: 99%